Pre-Marital Education: Concepts and Regulations in Indonesia and Malaysia - Kamarusdiana Kamarusdiana; Burhanudin Yusuf; Maman Rahman Hakim; Harapandi Dahri (Al-Ahkam, 2022)
One of the most significant ways to create a happy family and minimize divorce is premarital education. Indonesia and Malaysia are two countries that have realized it and have regulated it in the regulations of their respective countries. This paper focuses on studying the concept and regulation of premarital education in these two countries. This paper uses a normative juridical approach using library research and comparative law. This study found that premarital education aims to create household happiness to avoid divorce. Indonesia regulates it in the Decree of the Director-General of Islamic Religion by implementing the Office of Religious Affairs or institutions recognized by the Ministry of Religion. Meanwhile, in Malaysia, it differed according to state regulations, such as enactment 11 of 2003 amendment of the Islamic Family Law (Negeri Sembilan) 2003 Part II of Marriage Section 16 concerning Applications for Marriage Truth and carried out by the Malaysian Islamic Progress Office. Premarital education, although both aim to create a family and minimize divorce, in Indonesia, it only provides guidelines, while in Malaysia, it is a mandatory requirement for prospective brides to get married.